Environmental Awareness of Balinese Ecoculture in the Video Game Coral Island: Ludonarrative and Intertextuality Studies - Putri Ayienda Dinanti; Bias Yulisa Geni; Todo Sibuea (Leksema: Jurnal Bahasa dan Sastra, 2026)
The rise of farming role-playing games reflects a growing interest in using digital games to explore cultural identity and environmental themes. These games’ mechanics and storytelling intersect with environmental sustainability, deeply embedded in many social practices and traditions. Based on that phenomenon, this research examines how Balinese ecocultural elements are intertextualized in the story of one of the most recent farming simulation role-playing games called Coral Island. It employs Espen Aarseth’s ludonarrative model on the narrative structure of video game, as well as Julia Kristeva’s intertextuality theory in tandem with John Fitzsimmons’ to assess the relationship between cultural and environmental features of the gameplay. This research is guided by two central questions on how Balinese ecocultural elements are intertextually integrated in the game narrative and how these findings serve as instruments for ecological awareness. The findings reveal that through its intertextual portrayal of Balinese culture and environment like spirituality and ritual; traditional agriculture; mythological figures; and ocean stewardship, Coral Island bridges the gap between digital media and real-world issues. It shows the potential of video games to serve as powerful tools for cultural education and environmental awareness.